2020
DOI: 10.1108/bfj-08-2019-0633
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the triple helix model to upgrade the medical and aromatic plants value chain

Abstract: PurposeThe purpose of this research paper is to explore innovation activity between the three institutional spheres of government, universities and industry in the Palestinian MAPs sector, with the aim of supporting the growth of the sector through the THM.Design/methodology/approachThe research study employed a qualitative exploratory design. Twelve semi-structured interviews were conducted with participants from the three spheres of the THM related to the agricultural sector. Content analysis was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The mainstream open innovation literature is still insufficient to provide a complete and detailed picture of the factors that hinder the adoption and the implementation of open innovation in SMEs. Van de Vrande et al ( 2009 ) and Bigliardi and Galati ( 2016 ) have shown how specific open innovation practices and/or specific SME characteristics (e.g., size and sector) can generate different barriers, opening the way to more detailed reflections and in-depth case studies that focus on specific aspects related to the challenges SMEs undertake when engaging in open innovation, especially in inter-organisational projects (Santoro et al 2019 ; Sultan 2020 ). Most of the time, inter-organisational projects are structured and coordinated by following logics that are more suitable for large companies than for SMEs, with the result that SMEs tend to occupy weaker network positions and to depend on partners’ strategies instead of having control on the direction of their open innovation efforts (Dodourova and Bevis 2014 ).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The mainstream open innovation literature is still insufficient to provide a complete and detailed picture of the factors that hinder the adoption and the implementation of open innovation in SMEs. Van de Vrande et al ( 2009 ) and Bigliardi and Galati ( 2016 ) have shown how specific open innovation practices and/or specific SME characteristics (e.g., size and sector) can generate different barriers, opening the way to more detailed reflections and in-depth case studies that focus on specific aspects related to the challenges SMEs undertake when engaging in open innovation, especially in inter-organisational projects (Santoro et al 2019 ; Sultan 2020 ). Most of the time, inter-organisational projects are structured and coordinated by following logics that are more suitable for large companies than for SMEs, with the result that SMEs tend to occupy weaker network positions and to depend on partners’ strategies instead of having control on the direction of their open innovation efforts (Dodourova and Bevis 2014 ).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The mainstream open innovation literature is still insufficient to provide a complete and detailed picture of the factors that hinder the adoption and the implementation of open innovation in SMEs. Van de Vrande et al (2009) and Bigliardi and Galati (2016) have shown how specific open innovation practices and/or specific SME characteristics (e.g., size and sector) can generate different barriers, opening the way to more detailed reflections and in-depth case studies that focus on specific aspects related to the challenges SMEs undertake when engaging in open innovation, especially in interorganisational projects (Santoro et al 2019;Sultan 2020). Most of the time, interorganisational projects are structured and coordinated by following logics that are more suitable for large companies than for SMEs, with the result that SMEs tend to occupy weaker network positions and to depend on partners' strategies instead of having control on the direction of their open innovation efforts (Dodourova and Bevis 2014).…”
Section: Pre-competitive Collaboration and Smesmentioning
confidence: 99%
“…Despite the abundant literature on university-industry relationships in developed countries (Ritzen, 2020), the need to bring about the universityindustry-government linkages has been recently grasped in developing countries (Vaaland & Ishengoma, 2016). In Palestine, The weaknesses of UILs are well documented in the literature (Abu Hanieh et al, 2015;Khatib et al, 2013;Morrar et al, 2018;Sultan, 2020). Previous research proposes, among other causes, the lack of policies to facilitate UILs and the state of minimal resources of both Government and universities as determinants for poor collaboration.…”
Section: Overview Of Agriculture Sector In Palestinementioning
confidence: 99%
“…Although UILs offer mutually advantageous arrangements (Davey et al, 2011; Liu et al, 2020), a great deal of complexity exists when managing such cross-sector relationships in developing economies (Plewa et al, 2013). The poor infrastructure and the prevalence of small-scale producers and suppliers in developing countries extend this complexity (Béné, 2020; Sultan, 2020). In response, researchers emphasise understanding the nature of UILs to achieve effective university–industry collaboration (Awasthy et al, 2020; Bloedon & Stokes, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation